Effect of Bambara nut and cowpea intercropped with maize at different times on nutritive quality of maize for ruminant feeding - Olanite, J. A.; Muraina, T. O.; Ewetola, I. A.; Dele, P. A.; Ojo, V. O. A.; Anochirim, C. G.; Nwadike, N. F.; Saliu, T. A. (Malaysian Journal of Animal Science, 2017)
Effects of Bambara nut and cowpea planted with maize at different times on nutritive quality of maize forage were investigated. The study was laid out in a Completely Randomized Design and the treatments were combination of crop types (Bambara nut-maize (MB) and Cowpea-maize (MC) and planting times of legumes (2 wks before planting maize, 2WBPM and 2 wks after planting maize, 2WAPM), and sole maize (as control). An experimental field measuring 19 m 11 m was divided into 3 replicates; each replicate was sub-divided into 5 plots of dimension 3 m2 each, with 1 m and 2 m inter-plots and inter-blocks spacing respectively. Maize forage samples were harvested on each plot at 10 wks after planting, oven-dried, milled and analyzed to evaluate the chemical composition, mineral composition, in vitro gas production and post-incubation characteristics. Results revealed significant differences (P<0.05) among treatments with the highest (95.00%) and least DM (92.12%) values were recorded for MB 2WBPM and MC 2WAPM, respectively. CP values ranged from 10.36% in MB 2WBPM to 15.67% in MC 2WBPM but not significantly different from 14.19 % recorded for sole maize. Ash ranged from 7.00% in MB 2WAPM to 10.00% in sole maize. MC 2WBPM and sole maize had the highest (50.63%) and least (38.40%) in ADF content (P<0.05). ADL value (7.25%) observed in MB 2WBPM was the highest, compared to the least (5.00%) in sole maize. Sole maize recorded the least (40.40%) and highest (25.91%) cellulose and hemicellulose contents, respectively while MC 2WAPM had the highest (50.88%) and lowest (15.80%) values for cellulose and hemicellulose, respectively. Ca content (4.55g/kg) of MB 2WAPM was lower than the other treatments. P content ranged from 3.54 g/kg in MB 2WAPM to 12.02 g/kg in MC 2WAPM. Gas production rates only varied (P<0.05) at the 3rd, 6th, 24th and 48th hours of incubation. MB 2WBPM yielded highest values of short chain fatty acids (0.09 mol) and metabolizable energy (3.08 MJ/kg) while MB 2WAPM recorded the lowest values (0.01 mol and 2.57 MJ/kg) for the same parameters. MC 2WAPM and MB 2WAPM produced highest values of OMD (31.60 %) and DMD (37.50 %), respectively. In conclusion, sole maize had desirable CP, Ca, P with least fibre constituents. OMD and DMD of the sole maize were not significantly different from most of the legume mixtures. Better SCFA and ME also make MB 2WBPM treatment desirable.